HIMmaterial: exploring new hybrid media for immersive drawing and collage - Araújo, António (2020)
We propose an installation that explores Hybrid Immersive Models (HIM), the conjunction of digital VR panoramas with physical, handmade spherical perspectives and anamorphoses, as a new hybrid art medium that connects traditional drawing with digital, immersive art, creating a dialogue between material and immaterial forms of visual expression.